The Role of Using Generative Artificial Intelligence Applications in Improving University Students’ Academic Performance: A Field Study on a Sample of University Students - Ali, KADDOUR (Journal of Ecohumanism, 2026)
This study aims to analyze the role of generative artificial intelligence (AI) applications in improving the academic performance of university students, through a field study involving 63 undergraduate and postgraduate students. The study adopted a descriptive-analytical methodology based on a questionnaire covering four dimensions: the use of generative AI applications, educational benefits, cognitive skills, and academic performance. Statistical analysis employed percentages, Cronbach’s alpha coefficient, and Pearson’s correlation coefficient.The findings revealed that 76.2% of the sample had previously used generative AI applications. The results further demonstrated a statistically significant positive correlation between the use of these applications and improvements in academic performance. The study additionally confirmed that educational benefits and cognitive skills both contribute positively to improved student outcomes, reflecting the importance of conscious and structured use of AI in supporting university-level learning.